2015
DOI: 10.1136/bmjsem-2015-000063
|View full text |Cite
|
Sign up to set email alerts
|

Can clinicians and scientists explain and prevent unexplained underperformance syndrome in elite athletes: an interdisciplinary perspective and 2016 update

Abstract: The coach and interdisciplinary sports science and medicine team strive to continually progress the athlete's performance year on year. In structuring training programmes, coaches and scientists plan distinct periods of progressive overload coupled with recovery for anticipated performances to be delivered on fixed dates of competition in the calendar year. Peaking at major championships is a challenge, and training capacity highly individualised, with fine margins between the training dose necessary for adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 108 publications
(70 reference statements)
0
30
0
2
Order By: Relevance
“…Örneğin, önemli bir stres faktörünün veya kötü beslenme gibi nedenlerin de katkıda bulunabileceği vurgulanır. Bu nedenle UUPS tanısı için önkoşul uzun süre dinlenmeye rağmen performansta beklenmeyen bir düşüş olsa da, nedensel açıdan daha geniş bir bakış açısı gerekir (7). Antrenörler de, antrenman yükünün bir göstergesi olan "aşırı antrenman" teriminin bir anlamda kendilerini de sorumluluk altına sokması nedeni ile "açıklanamayan performans düşüklüğü" tanımını kullanmayı tercih edebilmektedir (1).…”
Section: Açıklanamayan Performans Düşüklüğü Sendromu (Unexplained-undunclassified
“…Örneğin, önemli bir stres faktörünün veya kötü beslenme gibi nedenlerin de katkıda bulunabileceği vurgulanır. Bu nedenle UUPS tanısı için önkoşul uzun süre dinlenmeye rağmen performansta beklenmeyen bir düşüş olsa da, nedensel açıdan daha geniş bir bakış açısı gerekir (7). Antrenörler de, antrenman yükünün bir göstergesi olan "aşırı antrenman" teriminin bir anlamda kendilerini de sorumluluk altına sokması nedeni ile "açıklanamayan performans düşüklüğü" tanımını kullanmayı tercih edebilmektedir (1).…”
Section: Açıklanamayan Performans Düşüklüğü Sendromu (Unexplained-undunclassified
“…Exceedingly high training loads and/or spikes in training load are a recognised risk factor for injury and illness, and fatigue 2 . Furthermore, illness and accumulating fatigue may result in the development of chronic underperformance 3 ; all of which can derail the athlete's season and may finish careers. Finding ways to reduce the risk of injury and illness is therefore a primary objective of the high-performance support team.…”
Section: Introductionmentioning
confidence: 99%
“…As an issue, this way of thinking allows us to investigate effects on doping from organizations such as teams, clubs, or federations that employ athletes. Many studies showed the role of an athlete's support personnel . However, here—again—individuals are considered analytic units to question their beliefs, knowledge, attitudes, or behaviors that are more or less conducive to doping.…”
Section: Introductionmentioning
confidence: 99%
“…Through their communication and monitoring with and about the athlete, the support personnel provides an essential follow‐up mechanism to produce a strong performance. This work collective also attempts to prevent problems such as overtraining, fatigue, and illnesses . These interactions lead to a more or less precarious professional integration of athletes.…”
Section: Introductionmentioning
confidence: 99%